(untitled) (Clinics, 2012)
OBJECTIVES: Pulmonary involvement in rheumatoid arthritis is directly responsible for 10% to 20% of all mortality. The best way to improve the prognosis is early detection and treatment. The forced oscillation technique is easy to perform and offers a detailed exam, which may be helpful in the early detection of respiratory changes. This study was undertaken to (1) evaluate the clinical potential of the forced oscillation technique in the detection of early respiratory alterations in rheumatoid arthritis patients with respiratory complaints and (2) to compare the sensitivity of forced oscillation technique and spirometric parameters. METHODS: A total of 40 individuals were analyzed: 20 healthy and 20 with rheumatoid arthritis (90% with respiratory complaints). The clinical usefulness of the parameters was evaluated by investigating the sensibility, the specificity and the area under the receiver operating characteristic curve. ClinicalTrials.gov: NCT01641705. RESULTS: The early adverse respiratory effects of rheumatoid arthritis were adequately detected by the forced oscillation technique parameters, and a high accuracy for clinical use was obtained (AUC.0.9, Se = 80%, Sp = 95%). The use of spirometric parameters did not obtain an appropriate accuracy for clinical use. The diagnostic performance of the forced oscillation technique parameters was significantly higher than that of spirometry. CONCLUSIONS: The results of the present study provide substantial evidence that the forced oscillation technique can contribute to the easy identification of initial respiratory abnormalities in rheumatoid arthritis patients that are not detectable by spirometric exams. Therefore, we believe that the forced oscillation technique can be used as a complementary exam that may help to improve the treatment of breathing disorders in rheumatoid arthritis patients.